A Note on the Effects of Switching Occurring in Sampling Period for Sampled-Data Bimodal Systems - Sen, Busra; Turker, Turker; Eren, Yavuz (IEEE, 2019)
This manuscript addresses the stability analysis of sampled modelling for bimodal linear and nonlinear switched system classes. Despite the fact that the switched systems have been investigated for decades, some deficiencies or neglected issues has attracted the researchers to provide more realistic modelling ideas. Hence, dealing the control problems in switched systems, sampled-data based modelling approach has become a prominent tool. We have presented the conditions to check the stability for this system classes by addressing the mismatching problem between the updating sequences of controller and active mode. Those conditions have been extended into the cases of bimodal linear and nonlinear system classes by considering the worst case analysis of mismatching problem and this phenomenon has been described explicitly with impressive examples.
Keywords: Stability; sampled-data systems; switched systems; STABILITY ANALYSIS; STABILIZATION; STABILIZABILITY; Automation & Control Systems; Computer Science